Allosteric control of nanomechanical DNA origami pinching devices for enhanced target binding. Issue 59 (6th July 2017) - Kuzuya, Akinori; Sakai, Yusuke; Yamazaki, Takahiro; Xu, Yan; Yamanaka, Yusei; Ohya, Yuichi; Komiyama, Makoto
Abstract : Significant enhancement of single-molecular binding of specific targets was achieved by allosterically controlling nanomechanical DNA origami pinching devices. Abstract : Significant enhancement of single-molecular binding to a miRNA target and bidentate and asymmetric conjugation of two distinct thiolated DNA strands to single gold nanoparticles (AuNPs) were visibly demonstrated, by introducing two groups of ligands into our nanomechanical DNA origami devices (DNA pliers) to construct allosterically controllable systems.